MAKNA KASIH DALAM KOMPOSISI “UNA LIMOSNA POR EL AMOR DE DIOS” KARYA AGUSIN BARRIOS MANGORE - Recky Rusman; Meyltsan Herbert Maragani (Institut Agama Kristen Negeri Manado, 2020)
Abstract This research aims to describe the meaning of love in the composition